Des arrangements autour de l’agriculture en périurbain : du lotissement agricole au projet de territoire - Monique Poulot (VertigO)
This article reads again in a critical way the « pas de deux agriculture-city » (Monteventi et al., 2008) in the last decades around the parisian metropolis. Three patterns of relationships emerge non in a simple diachronic sequence, but with many overlappings, retreats and shifts. The three of them are characterized by a overabundant invention of tools, constantly invested, especially intentionnal or interventional zonings, of uncertain efficiency. At the same time, there are new actors, like associations of new inhabitants or new networks of farmers in periurban areas ; these new actors call new forms of governance. Agricultural zoning characterizes the first phase ; then the countryside park ; and the agriurban program represents the third period and marks the advent of a new modality of space, the agriurban instead of the two old modalities, the urban and the rural.